Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007345
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for patients undergoing elective endoscopic retrograde cholangiopancreatography

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) involves cannulation of the ampulla of Vater and has diagnostic as well as therapeutic capabilities, but the number of non-therapeutic ERCPs is decreasing with time. 1 Endoscopic sphincterotomy, stone extraction and stenting are not without complications. The most widely recognised of these include bleeding, which occurs in 0.7 -2% of patients, perforation (0.3 -0.6%), pancreatitis (7%), cholangitis (1%) and cholecystitis (0.2 -0.5%). Procedure-related mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
16
0
9
Order By: Relevance
“…There is some evidence that a restricted use of antibiotics (dependent on the post‐procedure risk of cholangitis) is safe and effective . A recent Cochrane meta‐analysis concluded that while antibiotics reduced bacteraemia in patients undergoing elective ERCP; their benefit in those undergoing uncomplicated procedures was less evident . Further work is required to assess if prophylactic antibiotics (at the time of ERCP) may reduce the incidence of infectious complications after definitive surgery following PBD.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that a restricted use of antibiotics (dependent on the post‐procedure risk of cholangitis) is safe and effective . A recent Cochrane meta‐analysis concluded that while antibiotics reduced bacteraemia in patients undergoing elective ERCP; their benefit in those undergoing uncomplicated procedures was less evident . Further work is required to assess if prophylactic antibiotics (at the time of ERCP) may reduce the incidence of infectious complications after definitive surgery following PBD.…”
Section: Discussionmentioning
confidence: 99%
“…It can reduce the risk of cholangitis, bacteremia, and septicemia after ERCP. 85 Patients with PSC and end-stage liver disease should be evaluated to determine whether liver transplantations should be performed according to the standard guidelines. PSC has a significantly greater risk for the development of colorectal dysplasia and carcinoma in patients with UC.…”
Section: Hepatobiliary Manifestationsmentioning
confidence: 99%
“…Guidelines published by the American Society of Gastrointestinal Endoscopy (ASGE) in 2008 did not recommend the approach as a routine procedure, stating that it has no significant prophylactic effects . However, a subsequently published systematic review found that antibiotic prophylaxis prevents bacteremia and cholangitis . There is currently no consensus on the issue, and there has been very little discussion about potential adverse effects due to antibiotic prophylaxis for ERCP.…”
Section: Introductionmentioning
confidence: 99%